Variability of Serum Thyroglobulin Levels in Post- Thyroidectomy Patients with Well-Differentiated Thyroid Cancer: the ATA Guidelines - Silva, Frieda; Martin, Ralph J.; Figueroa, Jannette; Rincón, Fernando; Román, Diego (Puerto Rico Health Sciences Journal, 2016)
Objective: Evaluate the variability of stimulated serum thyroglobulin (Tg) levels in post-thyroidectomy patients with well-differentiated thyroid cancer (WDTC) and determine the frequency of undetectable Tg in patients with evidence of functional thyroid tissue after a 131-I whole-body scan (WBS). Methods: A retrospective record review of patients with WDTC referred to our clinic from 1990 to 2010. Demographic data, histology, staging, imaging studies, stimulated Tg values, and the presence if applicable of Tg antibodies (TgAb) were documented. The images of whole-body radioiodine scans were reviewed to assess the extent of functional thyroid tissue. Results: A total of 142 cases were evaluated with 417 studies. There were 112 women and 30 men; the median age was 47 years. The tumor histologies included 97 papillary (4 had the Hurthle cell variant), 33 papillary-follicular tumor, and 12 follicular tumors; 7 were multifocal. ATA classification was used; groups were divided into low (55%) and intermediate-high risk (45%). The final analysis comprised 84 patients, having among them 170 studies that included Tg values in their records. The cut-off value for Tg was 2.0 ng/ml, and for TgAb, it was 20 IU/ml or more. Residual functional tissue was present in 105 (62%) cases. Discordant Tg results were found in 55% of the low-risk patients; of those, only 3 had TgAb. In the intermediate- and high-risk group, 47% had discordant results; 2 cases had TgAb. Conclusion: The variability of the Tg levels and the high frequency of discordant results (positive WBSs with undectable Tg levels) bring into question the standard recommendation of conservative management for low-risk patients. Follow-ups should include a Tg assay and imaging studies.